Factors influencing decision making on donating organs for transplantation in the opinion of the respondents - study using the CAWI method - Majchrowicz, Bożena (Journal of Education, Health and Sport, 2022)
Introduction: Organ transplantation is a procedure of transferring living cells, tissues or organs within one organism or between two organisms. Despite the great achievements of transplantology and the legal basis regulating organ and tissue procurement and transplantation, there are still difficulties in overcoming social and psychological resistance related to this method of treatment and related to granting consent for organ donation. The aim of the study was to determine the knowledge of the factors influencing the decision to transplant organs among the respondents. Material and methods: The study was conducted using the CAWI method, where invitations were sent to a randomly selected group of respondents on the basis of specialized mailing lists, the research tool was a self-designed questionnaire. Participation in the study was anonymous and voluntary. Results and conclusions: Respondents have knowledge about transplantation. 52.4% of the respondents would agree that all organs should be taken from them after death in order to save the lives of other people, the remaining group was against it. The acceptance of organ donation may have an impact on the development of transplantology, especially thanks to its understanding by families who have to make decisions in this regard.